2018
DOI: 10.1186/s12915-018-0541-4
|View full text |Cite
|
Sign up to set email alerts
|

CDC42 controls the activation of primordial follicles by regulating PI3K signaling in mouse oocytes

Abstract: BackgroundIn mammalian females, progressive activation of dormant primordial follicles in adulthood is crucial for the maintenance of the reproductive lifespan. Misregulated activation of primordial follicles leads to various ovarian diseases, such as premature ovarian insufficiency (POI). Although recent studies have revealed that several functional genes and pathways, such as phosphoinositide 3-kinase (PI3K) signaling, play roles in controlling the activation of primordial follicles, our understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
(55 reference statements)
2
39
0
Order By: Relevance
“…Studies have shown that when FOXO3 is in the nucleus of the oocyte, it will maintain the follicles in a quiescent state. However, when FOXO3 is phosphorylated, it translocates out of the nucleus to promote follicle activation [ 28 ]. To confirm this, we performed IHC staining of FOXO3 ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that when FOXO3 is in the nucleus of the oocyte, it will maintain the follicles in a quiescent state. However, when FOXO3 is phosphorylated, it translocates out of the nucleus to promote follicle activation [ 28 ]. To confirm this, we performed IHC staining of FOXO3 ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the GO analysis of DEGs ( Figure 1 D), these results further confirm with single-cell data that the PTEN-AKT-FOXO3a signaling pathway is the key pathway for follicular activation. Next, we predicted the upstream factors that might be associated with follicle activation ( Table S3 ) and selected chemical drugs with the highest z-scores and verified their effects in the ovarian in vitro culture system, which is commonly used to study primordial follicle activation [ 21 , 28 , 38 ]. Among these drugs, curcumin was found to have a protective effect on the ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…But pcDNA3.1-KISS1 significantly decreased the mRNA levels of FOXO3, TSC2, and BAD (Figure 2C), which are the important downstream genes of the PI3K signaling pathway. Previous studies recommend that PIK3CG exhibits significant DNA copy number gains in ovarian cancer, compared to normal ovary in humans [42], PIK3C1 promotes the activation of primordial follicles [43], and moreover, in PDK1 depletion in oocytes depletes the majority of primordial follicles around the onset of sexual maturity and causes premature ovarian failure in mice [44]. In addition, FOXO3 depletion in GCs disrupts the normal ovarian follicular growth in mice [45], and a lower FOXO3 mRNA expression in GCs may lead to infertility in women [46].…”
Section: Discussionmentioning
confidence: 99%
“…The viral supernatants were collected via ultracentrifugation. As previously reported [ 61 , 62 ], we used a glass needle to inject the lentiviral vectors into the cortex of the neonatal ovaries at 1 dpp, selecting at least three parts. For each ovary, at least 0.3 μL of the lentiviral suspension (1×10 8 IU/mL) was injected.…”
Section: Methodsmentioning
confidence: 99%